2014
DOI: 10.1139/gen-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous germline excision ofTol1, a DNA-based transposable element naturally occurring in the medaka fish genome

Abstract: DNA-based transposable elements are ubiquitous constituents of eukaryotic genomes. Vertebrates are, however, exceptional in that most of their DNA-based elements appear to be inactivated. The Tol1 element of the medaka fish, Oryzias latipes, is one of the few elements for which copies containing an undamaged gene have been found. Spontaneous transposition of this element in somatic cells has previously been demonstrated, but there is only indirect evidence for its germline transposition. Here, we show direct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The Kimura substitution level is correlated with the age of transposition activity: low substitution levels indicate recent transposition events; higher substitution levels suggest old transposition events. The repeat landscape of the annotated P. phoxinus genome (Figure 2) indicates a high level of active, i.e., recent, transposition bursts (Watanabe et al, 2014). In fish genomes, active transposons accumulate at a faster rate than they decline (Shao et al, 2019), leading to an abundance of active transposons with low Kimura substitution levels (Böhne et al, 2012; Gao et al, 2016; Sotero-Caio et al, 2017), an exact pattern observed in TEs in the P. phoxinus genome.…”
Section: Resultsmentioning
confidence: 99%
“…The Kimura substitution level is correlated with the age of transposition activity: low substitution levels indicate recent transposition events; higher substitution levels suggest old transposition events. The repeat landscape of the annotated P. phoxinus genome (Figure 2) indicates a high level of active, i.e., recent, transposition bursts (Watanabe et al, 2014). In fish genomes, active transposons accumulate at a faster rate than they decline (Shao et al, 2019), leading to an abundance of active transposons with low Kimura substitution levels (Böhne et al, 2012; Gao et al, 2016; Sotero-Caio et al, 2017), an exact pattern observed in TEs in the P. phoxinus genome.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only some Tc1 -like elements (such as Tol1 , Tol2 , Passport , and Tana1 ) that were identified in bony fishes have been demonstrated to be transpositionally active ( Koga et al 2006 ; Clark et al 2009 ; Pujolar et al 2013 ; Watanabe et al 2014 ). Previous studies showed that most Tc1 -like elements in fishes are inactive because of stop codons, deletions, or frameshifts within their sequences ( Radice et al 1994 ; Reed 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, active Tc1/mariner transposons may be potentially used as molecular tools for transgenesis and insertion mutagenesis ( Pavlopoulos et al 2007 ; Voigt et al 2016 ). To date, only some Tc1 -like elements (such as Tol1 , Tol2 , Passport , and Tana1 ) in bony fishes are known to be both intact in their native form and transpositionally active ( Koga et al 2006 ; Clark et al 2009 ; Pujolar et al 2013 ; Watanabe et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the small DNA insertions and deletions detected in related genes among different species could have been generated by an ancient “paste-and-cut” transposition. Even almost fossilized DNA transposons, such as the medaka Tol1 element, are capable of undergoing transposition bursts [8]. Based on these findings, A. Koga proposed that DNA transposons, by acting as the major source of small DNA insertions and deletions, could have a more significant role in the evolution of their host genomes than was previously postulated.…”
Section: Highlights Of the Talksmentioning
confidence: 99%